IOC consensus statement on elite youth athletes competing at the Olympic Games: essentials to a healthy, safe and sustainable paradigm - Bergeron, M. F.; Côté, J.; Cumming, S. P.; Purcell, R.; Armstrong, N.; Basilico, L.; Burrows, K.; Charrin, J.-B.; Felix, A.; Groesswang, H.; Iwasaki, Y.; Kocher, M. S.; et al. (British Journal of Sports Medicine, 2024)
With the pronounced ongoing growth of global youth sports, opportunities for and participation of youth athletes on the world sports stage, including the Olympic Games, are expected to escalate. Yet, adolescence is a vulnerable period of development and inherently dynamic, with non-linear and asynchronous progression of physical, physiological, psychological and social attributes. These non-concurrent changes within and between individuals are accompanied by irregular and unpredictable threats and impediments. Likewise, the evident age-based criteria and conventional path for those youth athletes deemed eligible candidates for the Olympic Games are not well or consistently defined. Furthermore, the unstructured and largely varying policies and practices across the sporting International Federations specific to youth participation underscore the need to establish a contemporary universal paradigm that would enable elite youth athletes to navigate an individualised healthy pathway to personal, athletic and sport success. First, we reviewed and summarised key challenges facing elite youth athletes and the relevant evidence fundamental to facilitating and supporting central aspects of health and well-being, while empowering safe, sustainable and positive engagement during athletic and personal advancement and competition. Second, we developed and present a modern elite youth athlete model that emphasises a child-centred, practical framework with corresponding guidelines and recommendations to protect health and well-being while safely and favourably managing international sport competition. Our proposed evidence-informed paradigm will enable and support individualised pathways for healthy, well-rounded and sustainable positive engagement while achieving sport success for youth contending or aiming to compete at world-class international sporting events.